Digitalization Case Administration: Effectiveness Analysis Case Track Information System (SIPP) in Sinjai State Court - Jusniaty; Nurmiati; Armayana Ardi, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Case track information system is a computer application built/designed to conduct monitoring, supervision and internal control of the Center/Work Unit. This study aims to analyze the effectiveness of the Case Tracking Information System in facilitating the disclosure of case information at the Sinjai District Court, and to identify factors that influence the process of implementing SIPP in achieving the objectives of the Case Tracking Information System. The research method used is mix method which combines elements of quantitative research and qualitative research in order to answer your research question. Qualitative research with a descriptive approach, which allows the collection of primary and secondary data to answer the research questions posed. Quantitative reearch tools used are surveys and questionnaires using likert scale. sampling technique in this research is using purposive sampling method. Data were analyzed using data collection, data reduction and data presentation and conclusion drawing. The results showed that from the effectiveness measurement indicators, namely the understanding of the program from the apparatus is very good in mastering the application, but the community still needs guidance or guidelines in using the application. Target accuracy, can be said to have been achieved with the guidelines for preparing community satisfaction surveys with a Likert scale with very good indicators. Timeliness is effective in taking care of public needs and accelerating the decision-making process, but there are still problems in data entry due to poor networks. The achievement of goals can be said to be effective with the fulfillment of open and transparent access standards. As well as real changes can also be said to be effective with the existence of community satisfaction surveys that have provided positive results related to the services provided. While the factors that influence the effectiveness of the SIPP application in the Sinjai District Court are several two factors, namely (1) Internal factors such as public understanding of the SIPP application and (2) External factors such as the quality of the internet network in using applications that are not yet optimal.